Changes in physical properties of some proprietary safflower (Carthamus tinctorius L.) cultivars after film coating application - Dumanoglu, Zeynep (Bangladesh Journal of Scientific and Industrial Research, 2023)
Safflower is one of the economically important oil plants. There are some studies on safflower, but none on its seed properties. This study was carried out in the Biosystem Engineering laboratories of the Faculty of Agriculture of Bingöl University in 2021. The seeds of four different proprietary safflower cultivars were randomly sampled, and some of their physical properties were examined under two separate groups, that is, control and film-coated. The film coating material was applied in a single layer, and its effects on the seed size were compared between the study groups. The coating dose should be at a level that will not adversely affect the germination and emergence performance of the seed. As a result of the study, it was found that the safflower seeds were long and oval in shape. This study is important in that its results will help the researchers carry out mechanization and breeding studies on safflower. Bangladesh J. Sci. Ind. Res. 58(2), 129-132, 2023